2012
DOI: 10.1111/j.1365-2125.2012.04288.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic markers of CYP2B6 associated with efavirenz plasma concentrations in HIV‐1 infected Thai adults

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Interindividual variability in efavirenz plasma concentrations is associated with CYP2B6 genetic polymorphisms.• Twenty‐nine different alleles of the CYP2B6 gene are listed. CYP2B6*6, *9, *16, *26, *27 and *28 carriers are reported to be associated with slower efavirenz oral clearance.• The allelic variant 516G>T is associated with diminished activity of CYP2B6 and high efavirenz plasma concentrations are associated with an increase risk of neuropsychological toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…Overall, the allelic frequencies of the CYP2B6 SNPs detected in this study are consistent with a recent study in Thais (17). CYP2B6 499CϾG and 1375AϾG were the absent SNPs in this study, and CYP2B6 1459CϾT was rarely detected, which is consistent with previous reports from studies of Chinese patients (18,19) and Japanese patients (16).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, the allelic frequencies of the CYP2B6 SNPs detected in this study are consistent with a recent study in Thais (17). CYP2B6 499CϾG and 1375AϾG were the absent SNPs in this study, and CYP2B6 1459CϾT was rarely detected, which is consistent with previous reports from studies of Chinese patients (18,19) and Japanese patients (16).…”
Section: Discussionsupporting
confidence: 83%
“…Although the CYP2B6 516GϾT SNP is well known to be useful for predicting plasma efavirenz concentrations, little is known about the plasma efavirenz concentration prediction potential of the other two SNPs. Previous studies in Thais (13,17) and members of other ethnic groups (12,15,24) showed high plasma efavirenz concentrations in HIV-infected patients with the CYP2B6 516TT genotype while receiving rifampin. The frequency of this allele ranges from 15% in Asians up to 50% in Africans (11,15,25).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the means of efavirenz concentrations in the patients who carried heterozygous and homozygous mutants were 1.7 mg/liter and 1.2 mg/liter, respectively. Compared to a previous study in patients with HIV monoinfection, efavirenz concentrations of the corresponding patients were 2.0 mg/liter and 1.7 mg/liter, respectively (19). Patients in the current study were therefore more vulnerable to suboptimal efavirenz concentrations.…”
Section: Discussionmentioning
confidence: 64%
“…SNP 499C¡G was associated with high plasma efavirenz concentrations in Japanese subjects, and the remaining three SNPs, i.e., 64C¡T, 1375A¡G, and 1459C¡T, were reported in Chinese subjects (18). The CYP2B6 18492T¡C SNP was identified using HapMap (www.hapmap.org) data on Japanese and Han Chinese populations with an r 2 value of Ͼ0.8 (19). SNPs were genotyped at the Laboratory for Pharmacogenomics and Personalized Medicine, Ramathibodi Hospital, Mahidol University.…”
Section: Methodsmentioning
confidence: 99%
“…It is increasingly apparent that many polymorphisms in CYP2B6 are both relatively common and have a substantive effect on rates of drug metabolism [3, 6, 36, 37]. Hence, in screening for CYP2B6-mediated drug metabolism, it is important not only to document expression but also to define the haplotype being studied.…”
Section: Practical Recommendations: Cyp2b6 Expression and Polymorpmentioning
confidence: 99%